PWE-056 Delivery Of Bowelscope Screening – Experience From The Pilot Sites. (9th June 2014) - Bevan, R; Patnick, J; Loke, R; Saunders, B; Stebbing, J; Tighe, R; Veitch, A; Painter, J; Rees, CJ
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) is being expanded to include a single flexible sigmoidoscopy (FSIG) called BowelScope, offered to all 55 year olds in addition to biannual faecal occult blood testing from age 60–75 years. 6 pilot sites began BowelScope screening in May 2013, with a view to full English coverage by the end of 2016. Methods: We aim to describe practical issues involved in the delivery of BowelScope screening at the pilot centres, covering unit set-up, list format, and endoscopists delivering lists. A survey was sent to the 6 pilots for completion by screening staff. Data were also retrieved from the national BCSP database. Results: The first BowelScope list was delivered in the South of Tyne Screening Centre on 7 th May 2013. By December 2013, 4135 flexible sigmoidoscopy procedures had been performed in 6 centres. Centres have delivered 20–80 lists each, performing 2–7 lists per week. Sessions are run at varying times of day including evenings and Saturdays. 35 endoscopists undertake lists regularly, of whom 15 were already BCSP accredited. Other BCSP colonoscopists provide back up for lists when required. All non-BCSP were accredited through a combination of direct observation of procedural skills (DOPS) and an MQC exam. Specialist Screening Practitioners (SSPs) attend all lists, and are deployed in a variety of ways including: following patient journey, consenting or giving information, and supervision assistant SSPs. Table 1 shows details of screening lists by centre. Conclusion: BowelScope screening is being successfully delivered at the six pilot centres. Each centre has developed a screening template and organisational pattern that works around patient needs and existing endoscopy and bowel screening services. New patterns of working have been required to deliver BowelScope and challenges remain regarding adequate numbers of endoscopists. Disclosure of Interest: None Declared.